Study on chemical forms and solubility of lead in urban soils in Hangzhou city, China - FU Juan-lin; ZHANG Ming-kui; LI Ren-an (浙江大学学报. 农业与生命科学版, 2004)
The toxicity of lead (Pb) in urban soils is a major environmental concern. Understanding the accumulation and chemical forms of Pb in urban soils is necessary for prediction of the potential impact of soil Pb on human health. In this study, a total of 82 urban soil samples were collected from Hangzhou city, Zhejiang province, China, and chemical forms of Pb in the urban soils were investigated by a three-step sequential extraction. The soils were also subjected to determination of Pb solubility under different pH conditions. The results indicated that the Pb concentration in urban soils varied widely with land uses in such descending order as: commecial area (728 mg/kg) > scenic area and industrial area (100-105 mg/kg) > residential area (37.0 mg/kg) > agricultural area (23.6 mg/kg). Lead fraction in Hangzhou urban soils was mainly associated with Fe and Mn oxides and organic matters as well as clay minerals. The concentration of water-soluble Pb in the soils was very low, amounting to less than 258 μg/kg. The solubility of Pb in the urban soils was generally low when soil pH was in the range of 4 to 8. So presently the soil-Pb in soil may have only insignificant impact on the health of people living in the urban areas of Hangzhou.